Digital model data distribution in civil engineering contracts. Issue 3 (6th July 2015) - Peter E.D. Love, Jane Matthews; Professor Steve Lockley, Professor; Whyte, Andrew; Donaldson, James
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The use of digital-models to communicate civil-engineering design continues to generate debate; this pilot-work reviews technology uptake towards data repurposing and assesses digital (vs traditional) design-preparation timelines and fees for infrastructure. The paper aims to discuss these issues. Design/methodology/approach – Extending (building-information-modelling) literature, distribution-impact is investigated across: quality-management, technical-applications and contractual-liability. Project case-study scenarios were developed and validated with resultant modelling-application timeline/fees examined, in conjunction with qualitative semi-structured interviews with 11 prominent stakeholder companies. Findings – Results generated to explore digital-model data-distribution/usage identify: an 8 per cent time/efficiency improvement at the design-phase, and a noteworthy cost-saving of 0.7 per cent overall. Fragmented opinion regarding modelling utilisation exists across supply-chains, with concerns over liability, quality-management and, the lack of Australian-Standard contract-clause(s) dealing directly with digital-model document hierarchy/clarification/reuse. Research limitations/implications – Representing a small-scale/snapshot industrial-study, findings suggest that (model-distribution) must emphasise checking-procedures within quality-systems and, seek precedence clarification for dimensioned documentation. Similarly, training in specific file-formatting (digital-model-addenda) techniques, CAD-file/hard-copy continuity, and digital-visualisation software, can better regulate model dissemination/reuse. Time/cost savings through digital-model data-distribution in civil-engineering contracts are available to enhance provision of society's infrastructure. Originality/value – This work extends knowledge of 3D-model distribution for roads/earthworks/drainage, and presents empirical evidence that (alongside appropriate consideration of general-conditions-of-contract and specific training to address revision-document continuity), industry may achieve tangible benefits from digital-model data as a means to communicate civil-engineering design.